Kurikulum Bagi Anak Berkebutuhan Khusus (ABK) - Marani, Aslan (Faculty of Ushuluddin and Humanities, 2017)
Curriculum change occurred nowadays shows that the curriculum is prone to social changes. Although the changes remain happened, there seems no curriculum which distinguishes its use between normal students and students with special needs (either physical or mentality). In fact, the curriculum should be enjoyed not only by the normal students but also the students with special needs. Hence, they can obtain equal education system without feeling a sense of discrimination from the government. Although the curriculum is the same, teachers may apply different strategies and methods. Hence, the teachers are not only professional in teaching, but also has specific competence than those who teach normal students. What I mean competence here is not professional, pedagogy, personality, or social competences. Rather, it is a spiritual competence where teachers are teaching by heart, not by material (money).